Licitações sustentáveis no âmbito da secretaria de Estado de educação e qualidade do ensino do Amazonas - Gomes, Cristine Cavalcanti (2017)
The bidding procedure for the acquisition of goods and services by the Public Administration is mainly aimed at selecting the most advantageous proposal for the State, ensuring the equality between bidders. In this context, the legislative amendment promoted by Law no. 12.349, dated December 15, 2010, in art. 3º of Law N. 8.666 of June 21, 1993, included in the list of objectives of the bidding procedure, along with compliance with the constitutional principle of isonomy and the selection of the most advantageous proposal, the promotion of sustainable national development, making possible the insertion Of sustainability criteria in the selection of proposals for the acquisition of goods and services by the State. By exercising its economic power by acquiring products and services that meet sustainability criteria, the State encourages the adoption of sustainable practices by private initiative and fosters transindividual benefits that may come from this model of public contracting. The problem proposed in this research is to verify how the State of Amazonas, through the State Department of Education and Quality of Education - SEDUC, has conducted public procurement, regarding the stipulation and observation of sustainability criteria, aiming at Analyze the implementation of environmental sustainability guidelines, established in Decree n. 7.746 / 2012, in the purchases made by the Executive Power of the State of Amazonas, specifically those approved in the year 2016 by that Secretary. Therefore, after approaching sustainability and sustainable bids, in aspects such as concept and normative evolution, it analyzes all bidding procedures approved in the year 2016 to meet the needs of the State Department of Education and Quality of Education - SEDUC. The obtained results allowed to conclude that the State of Amazonas did not insert in its procedures the criteria of sustainability with environmental bias. In this context, it examines the factors that hypothetically contributed to the non-implementation of the new legal objective and the previous and subsequent mechanisms for the control of administrative activity, with the objective of promoting the promotion of sustainable national development. The present research was developed through the method of deductive approach, and the data collection was done through the qualitative, bibliographical and documentary research. KEYWORDS: procedure; Bidding process; sustainability; products; services.